GRYLLOBLATTIDS OF THE FAMILY IDELIIDAE (INSECTA: GRYLLOBLATTIDA) FROM THE LOWER PERMIAN OF THE URAL MOUNTAINS - Aristov D.S. (My University, 2002)
A new genus of the family Ideliidae, Tshekardelia media gen. et sp. nov., is described from the locality of Tshekarda, the Lower Permian of the Ural Mountains. The species Sylvidelia latipennis Martynov, 1940, is redescribed.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская